The modification of surface, size and shape of barium zirconate powder via salt flux - Charoonsuk, Thitirat; Kolodiazhnyi, Taras; Vittayakorn, Naratip (My University, 2019)
The “top-down” process via direct conversion of the micro (μm)-to-submicroscale (sub-μm) particle was applied in this work by using eutectic chloride salts to prepare BaZrO3. The particle size at optimum condition could be decreased by more than 10 times from 2.1 ± 0.9 μm to 168 ± 23 nm without destroying the 1:1 of Ba:Zr stoichiometry. The uniform sub-μm-BaZrO3 powder was sintered in order to obtain ~98% dense ceramic at 1400°C/10 h, which is significantly lower than the 1650°C in normal cases. The microwave dielectric constant, tan δ, and quality factor were also determined. Furthermore, this method also was applied to lead-free piezoelectric material in the 0.87BaTiO3–0.13BaZrO3–CaTiO3(0.87BT–0.13BZ–CT) system. The particle size of 0.87BT–0.13BZ–CT was reduced greatly from >10 µm to 2.8 ± 0.4 µm. It can be proved that salt flux dissolution method enables high-purity with uniform sub-micro/nanometer powder production in one step by using simple laboratory equipment and low-cost raw materials.
Keywords: BaZrO3; microwave dielectric ceramic; nanoparticles; salt-flux dissolution